Combination of immunotherapy with chemotherapy and radiotherapy in lung cancer: is this the beginning of the end for cancer?. (5th April 2018) - Lazzari, Chiara; Karachaliou, Niki; Bulotta, Alessandra; Viganó, Mariagrazia; Mirabile, Aurora; Brioschi, Elena; Santarpia, Mariacarmela; Gianni, Luca; Rosell, Rafael; Gregorc, Vanesa
Immune checkpoint inhibitors have significantly improved overall survival with an acceptable safety profile in a substantial proportion of non-small cell lung cancer (NSCLC) patients. However, not all patients are sensitive to immune checkpoint blockade and, in some cases, programmed death 1 (PD-1) or programmed death ligand 1 (PD-L1) inhibitors accelerate tumor progression. Several combination strategies are under evaluation, including the concomitant or sequential evaluation of chemotherapy or radiotherapy with immunotherapy. The current review provides an overview on the molecular rationale for the investigation of combinatorial approaches with chemotherapy or radiotherapy. Moreover, the results of completed clinical studies will be reported.